The Effect Of Training Needs On Human Resources Development In Public Works Offices (PU) Jeneponto District - M. Yusuf Alfian Rendra Anggoro KR; Naidah Naidah; Samsul Rizal; Serry Adelia; Kardina Kardina (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the extent of the influence of training needs on human resource development at the Jeneponto Regency Public Works Office. This type of research used a quantitative approach. The processed data is the result of respondents from the employees of the Jeneponto Regency Public Works Office (PU) as many as 30 respondents. The data analysis method used in this study uses simple linear regression, namely the approach method for modeling the relationship between one dependent variable and one independent variable using SPSS v 18. Based on the data analysis that has been done, the simple regression equation model is obtained Y= 4.858 + 0,807 which means that the influence of the X variable has a positive effect on the development of Human Resources and from the results of the t test analysis, a significant value of 0,01 (6.772 t table 2.048) dan koefisien regresi bernilai positif sebesar 0,788.